2009
DOI: 10.1007/s11096-009-9316-x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Clostridium difficile infection testing and treatment trends at a large tertiary care teaching hospital

Abstract: Increased rates of CDI testing and use of alternative therapies was observed at a time when the hypervirulent strain was first identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This study demonstrated that the prevalence of CDI in at risk adult hospitalized patients (patients with diarrhea with no other identifiable cause and recent antimicrobial exposure) in two large hospitals in Bangladesh was 9%. This prevalence is similar to that reported in other South Asian countries and the United States [11,22,23]. Clinicians at these two hospitals were not testing for C. difficile until this study was conducted, highlighting the importance of this under-diagnosis.…”
Section: Discussionsupporting
confidence: 82%
“…This study demonstrated that the prevalence of CDI in at risk adult hospitalized patients (patients with diarrhea with no other identifiable cause and recent antimicrobial exposure) in two large hospitals in Bangladesh was 9%. This prevalence is similar to that reported in other South Asian countries and the United States [11,22,23]. Clinicians at these two hospitals were not testing for C. difficile until this study was conducted, highlighting the importance of this under-diagnosis.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast with this literature demonstrating a temporal increase in incidence in IBD and non‐IBD patients, there has been limited examination of change in characteristics of affected patients or outcomes after C. difficile infection over the past decade. In one such analysis not restricted to IBD patients, Salazar et al22 did not find a difference in the demographic characteristics of C. difficile ‐positive patients in 2005–2006 compared to 2006–2007 at a single tertiary referral center. In the present study, while there was no difference in mean age of C. difficile‐ IBD patients across the three study years, there was a modest increase in the general comorbidity as measured using the Elixhauser index.…”
Section: Discussionmentioning
confidence: 97%
“…Previous study in a large tertiary care teaching hospital in U.S. reported that metronidazole was the most commonly used drug (81.6%) for CDI treatment. 18 Study in a French university hospital also reported metronidazole alone was used in 73.5% for CDI treatment despite severe CDI was observed in 53.9% of all CDI patients. 19 In our study, metronidazole was started in 83.9% of CDI cases because most patients had non-severe CDI.…”
Section: Discussionmentioning
confidence: 99%